Quantitative assessment of OCT and OCTA parameters in diabetic retinopathy with and without macular edema: single-center cross-sectional analysis - Cui, Yanyan; Feng, Dongfan; Wu, Changlong; Wang, Ping; Cui, Ruoxi; Wang, Xiaokun; Chang, Weiwei; Shang, Weiwei; Zhao, Bojun; Liu, Jing; Qin, Xuejiao (Frontiers in Endocrinology, 2024)
The retinal and choroidal parameters were analyzed to understand the impairment of micro-circulation of both retina and choroid in patients with diabetic retinopathy (DR).Fifty-five treatment naïve non-proliferative diabetic retinopathy (NPDR) patients (75 eyes) with type 2 diabetes mellitus (T2DM), including 28 patients (36 eyes) with diabetic macular edema (DME), 27 patients (39 eyes) without DME, and 25 healthy subjects (47 eyes), were enrolled in this study. The following parameters of DR patients with and without DME were evaluated: the foveal avascular zone area (FAZ-a), FAZ perimeter (FAZ-p), FAZ circularity index (FAZ-CI), total sub-foveal choroidal area (TCA), luminal area (LA), stromal area (SA), choroidal vascularity index (CVI), choriocapillaris flow area percentage, superficial capillary plexus (SCP) and deep capillary plexus (DCP).SCP, DCP and the percentage of choriocapillaris flow area were significantly different between DR patients with and without DME. The DR patients presented lower LA, CVI and FAZ-CI compared to that of health controls (all p＜0.05). The percentage of choriocapillaris flow area in DR patients with and without DME was significantly lower than health controls (p ＜ 0.05). SCP and DCP were significantly correlated with FAZ-a and FAZ-p but presented insignificant associations with FAZ-CI.OCT and OCTA parameters, such as LA, CVI, FAZ-CI and the percentage of choriocapillaris flow area were reduced compared to that in controls, indicating the micro-circulations of retina and choroid in macular area were impaired in DR patients regardless with DME and without DME.